Hypercalcemia in Small Lymphocytic Lymphoma with an Elevated Parathyroid Hormone-Related Peptide Associated with Early Richter Transformation - Ashish Bains; Pedro Covas; Olga Timofeeva; Michael Bromberg (Case Reports in Hematology)
Hypercalcemia in malignancy is associated with multiple mechanisms and occurs in up to 20–30% of cancer patients. We report a case of small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL) associated with hypercalcemia and an elevation in parathyroid hormone-related peptide (PTHrP) in the setting of a Richter transformation. Real-time reverse transcriptase PCR on lymph node biopsy specimens obtained before and after transformation showed an 8-fold increase in PTHrP mRNA levels and about 2-fold decrease in the levels of its cognate receptor PTHR1. The findings of this case suggest that parathyroid hormone-related peptide might be useful in monitoring a specific group of patients with SLL/CLL who develop hypercalcemia during the course of their disease and could suggest an autocrine-like mechanism involving PTHrP in Richter transformation.